3D Ferroconcrete‐Like Aminated Carbon Nanotubes Network Anchoring Sulfur for Advanced Lithium–Sulfur Battery. Issue 25 (11th July 2018) - Yan, Min; Chen, Hao; Yu, Yong; Zhao, Heng; Li, Chao‐Fan; Hu, Zhi‐Yi; Wu, Pan; Chen, Lihua; Wang, Hongen; Peng, Dongliang; Gao, Huanxin; Hasan, Tawfique; et al.
Abstract: To address the serious capacity fading in lithium–sulfur batteries, a 3D ferroconcrete‐like aminated carbon nanotubes network with polyaniline coating as an effective sulfur host to contain polysulfide dissolution is presented here. In this composite, the cross‐linked aminated carbon nanotubes framework provides a fast charge transport pathway and enhancement in the reaction kinetics of the active material to greatly improve the rate capability and sulfur utilization. The ethylenediamine moieties provide strong adhesion of polar discharge products to nonpolar carbon surfaces and thus efficiently prevent polysulfide dissolution to improve the cycle stability, confirmed by density functional theory calculations. The outside polyaniline layers structurally restrain polysulfides to prevent the shuttle effect and active material loss. Benefiting from these advantages, the synthesized composite exhibits a high initial capacity of 1215 mAh g −1 and a capacity of 975 mAh g −1 after 200 cycles at 0.2 C. Even after 200 cycles at 0.5 C, a capacity of 735 mAh g −1 can be maintained, among the best performance reported. The strategy in this work can shed some light on modifying nonpolar carbon surfaces via the amination process to chemically attach sulfur species for high‐performance lithium–sulfur batteries. Abstract : A 3D ferroconcrete‐like aminated carbon nanotube network with polyaniline surface coating layer is designed to anchor sulfur species. The as‐synthesized cathode composite demonstrates high capacity and long cycle stability for lithium–sulfur batteries, suggesting that amination of nonpolar carbon materials is a promising strategy for effective sulfur species anchoring.